RESEARCH MARKETING STANDARDS FOR CHICKEN EGG QUALITY PARAMETERS INTENDED FOR CONSUMPTION : Evaluating Quality Indicators and Market Expectations for Fresh Eggs in Kosovo - Mestani, Mergim; Mehmeti, Ibrahim; Zeqiri, Medin (Polish Journal of Natural Sciences, 2025)
The study revealed significant differences between market and fresh eggs across various parameters, as indicated by the calculated P-values. Market eggs exhibited a mean weight of 62.30 g, slightly lower than fresh eggs at 65.89 g (P=0.0001). Eggshell weight was lower in market eggs (7.35 g) compared to fresh eggs (7.97 g), with a significant difference (P=0.0186). However, eggshell thickness showed no statistically significant difference between the two groups (market: 0.41 µm, fresh: 0.43 µm; P=0.1626). Yolk weight was significantly higher in fresh eggs (15.31 g) compared to market eggs (14.37 g; P=0.021), with a more intense yolk color in fresh eggs (RYCF: fresh 12.35, market 11.45; P=0.0259). Haugh unit values were substantially higher in fresh eggs (88.46) compared to market eggs (76.57; P=0.0006), accompanied by a smaller air cell size in fresh eggs (3.47 mm) compared to market eggs (4.78 mm; P=0.0044). Based on the findings, fresh eggs meet the criteria for superior quality, being classified as "L" class based on their weight and "extra" class due to their smaller air cell size. On the other hand, market eggs may fall into lower quality classes, such as "M" class, due to their lower weight and larger air cell size. Nevertheless, both types of eggs are deemed suitable for consumption according to established guidelines. Continuous research is crucial for refining egg quality standards and meeting consumer expectations.